Design and Manufacturing Motorized Trike Drift Using 110 cc Suzuki Jet Cooled Gasoline Engine - Romiyadi; Adi Febrianton; Purnama Irwan (Jurnal Teknik Mesin, 2021)
Motorized trike drift is a unique means of transportation that is adapted from a bicycle with 3 wheels, 2 wheels at the rear and 1 wheel at the front for steering control. The purpose of the study was to design and manufacture of motorized trike drift  using gasoline engine Suzuki Jet Cooled 110 cc as a power source. From the process of designing and manufacturing, has produced a motorized trike drift using  gasoline engine Suzuki Jet Cooled 110 cc as a power source. The transmission system used is a chain and sprocket. From the test results, the speed of motorized trike drift can reach 40 km /hour, but for convenience, the speed limit is 20-25 km / hour. For fuel use, 1 litre of fuel can be used within 30 minutes or within a distance of 15-20 km.